Presentation pattern and survival rate of retinoblastoma following chemotherapy: a prospective study - Mayor Orezime Atima; Ugbede Idakwo; Oyeronke Komolafe; Shimizu Eisuke; Nakayama Shintaro; Emmanuel Oluwadare Balogun; Emeka John Dingwoke; Ayodele Jacob Orugun; Kenneth Onosigho Ukumobe; Jah Douglas Pam; Amaka Aladiuba (BMC, 2023)
Abstract Background This study presents the clinical pattern of presentation and survival rate of retinoblastoma, which is the most prevalent form of pediatric intraocular cancer. The aim of this study is to provide baseline information about the clinical presentation and management of retinoblastoma at ECWA Eye Hospital. Additionally, the study identifies priority areas for enhancing medical care for children diagnosed with this cancer. ECWA Eye Hospital, situated in Kano State, Nigeria, is a specialized eye center located in the North-Western region of the country. Methods A prospective study spanning five years was conducted at ECWA Eye Hospital to investigate clinically diagnosed cases of retinoblastoma. The study took place from January 2018 to December 2022. The patients received standardized pre-medication and chemotherapy protocols for retinoblastoma. Subsequently, a five-year follow-up was conducted to monitor the patients' progress. The collected data was analyzed, descriptive statistics were generated, and the survival rate was calculated. Results During the five-year study period, a total of 35 cases of retinoblastoma were diagnosed. The patients had an average age of 3.21 ± 1.32 years. The most common presentation patterns observed were fungating ocular mass and proptosis. Among the cases, there were 10 instances of bilateral proptosis and 25 instances of unilateral proptosis. While no patients exhibited bilateral leukocoria, eight cases of unilateral leukocoria with anterior segment seedlings were identified. The additional patterns of presentation are proptosis, leukocoria, fungating orbital mass, redness and loss of vision. The mortality rate was 80% (28 cases), while the survival rate was 20% (7 cases). Notably, all the survivors had unilateral retinoblastoma. Conclusion The majority of cases observed at ECWA Eye Hospital involve advanced retinoblastoma. In low-resource settings where alternative treatment options are limited, chemotherapy is considered a viable treatment option. Early presentation of retinoblastoma in patients may lead to a higher survival rate when chemotherapy is administered.